Optimization of Palm Bunch Ash-Based Catalysts for the Transesterification of Waste Cooking Oil into Biodiesel - Sakhi, Fillah M.; Santoso, Aman; Sumari, Sumari (Universitas Tadulako, 2025)
The increasing dependence on fossil fuels to meet fuel needs has caused several problems, such as air pollution, greenhouse effects, unpleasant odors, and loud noises. This research aims to design an alternative fuel in the form of biodiesel by applying a heterogeneous catalyst based on palm bunch to synthesize biodiesel through transesterification. The research stages include activating the active sites of palm bunches through calcination at temperatures of 400 °C, 500 °C, and 600 °C; refining waste cooking oil; esterification; and transesterification. The active components of palm bunch ash (PBA) were characterized using XRF and alkalinity testing. XRF results indicated that PBA contains active basic compounds such as K₂O and CaO, crucial in catalytic activity. Physical-chemical property testing revealed that the synthesis achieved the highest yield of 93.744 %. The results of the physical-chemical characteristic tests produced the best density with an average of 0.888 g mL⁻¹, and the lowest viscosity with an average of 3.79 cSt at 40 °C with an iodine number of 80.116 g I₂ 100 g⁻¹, a saponification number of 170.57 mg KOH g⁻¹, and a refractive index of 1.445. The catalyst demonstrated stable performance up to three reuses with yields ranging from 80–90 %. FTIR spectra showed strong absorption bands at 1172–1165 cm⁻¹, indicating C-O-CH₃ stretching from methyl esters. GC-MS analysis showed that the biodiesel consists of various fatty acid methyl esters (FAME), with the main component being methyl oleate, which appears at a retention time of 37.096 minutes with an area of 40.31 %. So it is shown that PBA catalysts have an excellent potential for commercial applications as they can reduce dependence on fossil fuels by utilizing household waste.